Strategizing directions of financial aspect development in the corporate security system of an industrial enterprise - Serhiienko, Olena; Volosnikova, Natalia; Yehorova, Yulia; Makarchuk, Kateryna; Sokolova, Natalia (TOV "Fintehalyans", 2023)
The article develops and substantiates the concept of the financial strategy of the corporate insurance system. The scheme of formation of the financial strategy of corporate security at an enterprise is analyzed. It is proven that an important criterion for ensuring the effectiveness of the financial strategy of an enterprise corporate security system is to detail and specify its functions, which are divided into two components: the processes of formation and use of enterprise financial resources. It is emphasized that in order to implement an effective strategy for achieving competitive advantages, it is necessary to ensure the appropriate level of management system development which is capable of ensuring the integration of functional areas of its activity. The achievement of interaction and coherence of implemented measures in each of the areas of an enterprise activity should be coordinated according to the general strategy. It has been confirmed that the economic effect plays an important role in the economic development of the corporate security system. In addition, the requirement of consistency of material, financial, information and other types of resource flows of integrated logistics processes at enterprises is particularly relevant. We made the conclusion that one of the tasks of the corporate security system in terms of financial resource provision management is tracking the intensity and targeting of resource provision flows, forecasting costs and benefits when achieving mutual goals of both the corporate security system and local elements of corporate security.

У статті розроблено та підтверджено концепцію фінансової стратегії для систем корпоративного страхування. Проаналізовано формування плану фінансової стратегії безпеки підприємства. Практика довела, що важливим критерієм забезпечення ефективності фінансової стратегії підприємства є уточнення її функцій, які поділяються на дві частини: процес формування та процес використання фінансових ресурсів підприємства. Підкреслено, що для реалізації ефективної стратегії досягнення конкурентної переваги необхідно забезпечити належний рівень розвитку системи менеджменту, здатної забезпечити інтеграцію функціональних сфер її діяльності й досягти взаємодії та узгодженості різних функціональних областей. Заходи, що впроваджуються в кожній сфері діяльності підприємства, повинні узгоджуватися із загальною стратегією. Доведено, що економічний ефект системи страхування підприємств відіграє важливу роль у розвитку економіки. Крім того, наголошено, що в комплексному логістичному процесі підприємства особливо важливими є вимоги узгодженості різноманітних потоків ресурсів, таких як матеріали, фінанси та інформація. Зроблено висновок про те, що з точки зору управління постачанням фінансових ресурсів важливими завданнями системи безпеки підприємства є відстеження інтенсивності та актуальності потоків постачання ресурсів, а також прогнозування витрат і вигод, за яких система безпеки підприємства та її локальні елементи досягають спільних цілей безпеки.
Стратегування напрямів розвитку фінансової складової в системі корпоративної безпеки промислового підприємства
Keywords: financial flow; financial resources; financial strategy; management of financial resources; system of corporate security of an enterprise; фінансовий потік; фінансові ресурси; фінансова стратегія; управління фінансовими ресурсами; система корпоративного убезпечення підприємства